Assessment of environmental degradation and conservation in the Maracanã River Basin, eastern amazon - Raiol, Lucas Lima; Rocha, Yuri Antonio da Silva; Lima, Aline Maria Meiguins de; Velastegui-Montoya, Andrés (Frontiers in Environmental Science, 2025)
Coastal basins stand out for their continent-estuary interface and connection as corridors of mangrove forests. The Maracanã River Basin (MRB) represents this environment, holding various ecosystem services for the component municipalities, protected areas with highly sensitive environments and water demand, and potential for multiple water uses. The proposed aim was to identify areas of degradation and environmental conservation in the MRB using the Blueprint model as support for water resource management. The methodology involved the application of the Blueprint model in the MRB, based on land use and cover information, rainfall, and characterization of the ecological units. The results showed that the MRB basin predominantly exhibits the degradation and restoration/connectivity classes in the Annual Blueprint (ABP) and Dry Blueprint (DBP), respectively. On the other hand, the Rainy Blueprint (RBP) predominantly exhibits Environmental Integrity. Statistical tests showed significant differences between ABP-RBP and DBP-RBP, which can be explained by the fact that on an annual scale of analysis, Blueprint classes are more heterogeneous, with a tendency toward environmental integrity, and intermediate classes in the rainy period; in the dry period, restoration and connectivity and degradation classes predominate. The correlation analysis indicates that natural vegetation cover shows a significant correlation with annual precipitation, rainy and dry quarters. These results provide significant insight into understanding the dynamics of degradation and conservation areas, assisting decision-makers in the environmental planning of the basin. In addition, the climatic component showed a differential response on annual and seasonal scales, acting as a modulating agent of the indicators.